Endogenous cortisol in keratinized matrices: Systematic determination of baseline cortisol levels in hair and the influence of sex, age and hair color. (March 2018) - Binz, T.M.; Rietschel, L.; Streit, F.; Hofmann, M.; Gehrke, J.; Herdener, M.; Quednow, B.B.; Martin, N.G.; Rietschel, M.; Kraemer, T.; Baumgartner, M.R.
Highlights: Baseline cortisol levels are generally low in hair. A standardized analytical method for hair cortisol measurement is needed. Hair cortisol is age dependent and influenced by sex and hair color. Age-dependent normative baseline cortisol levels are highly recommended. Abstract: The measurement of hair cortisol is increasingly used to measure long-term cumulative cortisol levels and investigate its role as an important stress mediator. In this study a comparative statistical analysis of five independent studies (all analyzed in our laboratory) was performed to investigate baseline ranges of cortisol values in hair and evaluate potential influences of sex, age and hair color. Cortisol concentrations in hair of 554 subjects were measured and a comparative statistical analysis was performed. The analysis showed that cortisol levels significantly differ depending on age. The toddler group (7 months (0.6 years) to 3 years) showed significantly higher values (median 10 pg/mg, p -value < 0.0001, d  = 0.78) than the adolescent group. The adolescent groups showed significantly lower ( p -value < 0.0001, d  = 0.58 and p  < 0.0001, d  = 0.13) values (median 2.4 pg/mg and 2.8 pg/mg) than the adult group (median 5.8 pg/mg). Furthermore, in the adult group men showed significantly higher cortisol values than women ( p -value < 0.05, d  = 0.17). This effect could not be seen in the adolescent group. Black hair showed higher cortisol concentrations than blond hair ( p -value < 0.0001, d  = 1.3). In addition, two rounds of interlaboratory comparisons for hair cortisol samples between four laboratories revealed very consistent results. Our results demonstrate that baseline cortisol levels are generally low in hair thus making a standardized and well-elaborated analytical method indispensable for accurate determination. Age-dependent normative baseline cortisol levels (toddlers, adolescents and adults) are highly recommended based on the comparative analysis comprising five independent studies.